An assessment of facilitative leadership, communication quality and trust on public-private partnership success - Mohd Som, Rafedzah; Ismail, Ismi Arif; Omar, Zoharah; Alias, Siti Noormi; Asimiran, Soaib (Emerald Publishing, 2023)
Purpose “ This study aims to test a public“private partnership (PPP) success model by examining the direct effects of two input factors (facilitative leadership and communication quality) on an outcome factor, namely, PPP success (PPP project success and PPP relational success), as well as the mediating effect of trust as a process factor on these relationships. Design/methodology/approach “ The present research uses the sociotechnical systems theory as the guiding framework. This is a quantitative study that uses a questionnaire survey and purposive sampling. The respondents comprise 266 public and private sector employees who have been involved in various PPP projects. The data gathered from the survey are analysed using SPSS and structural equation modelling (AMOS version 23.0). Findings “ The findings of this study indicate that facilitative leadership, communication quality and trust are positively correlated with PPP success, that is, PPP relational and PPP project success. Trust is found to mediate the relationship between facilitative leadership and communication quality with PPP success. Practical implications “ This paper upholds the importance of facilitative leadership, communication quality and trust in a PPP setting. Originality/value “ This study enriches the knowledge of PPP projects regarding facilitative leadership, communication quality and trust. It also discusses the vital role of these variables in ensuring PPP success.